2020
DOI: 10.1177/1758573220957631
|View full text |Cite
|
Sign up to set email alerts
|

Early functional mobilization for non-operative treatment of simple elbow dislocations: a systematic review

Abstract: Purpose This systematic review aims to elucidate a non-operative rehabilitation program that optimizes recovery based on published approaches and outcomes. Methods Searches of four databases from inception to 1 January 2020 were performed to identify clinical studies addressing the non-operative management of simple elbow dislocations. Results Of 2435 studies that were eligible for title screen, 15 studies satisfied inclusion criteria. Three randomized control studies demonstrated that early mobilization exped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
0
8
0
1
Order By: Relevance
“…The rest consisted of level III-V evidence. 4 , 11 , 14 , 32 As is typical for surgical management of orthopedic conditions, it is hard to reduce the risk of bias for surgical interventions. A narrative review is discussed regarding the most current and relevant literature on AED.…”
Section: Resultsmentioning
confidence: 99%
“…The rest consisted of level III-V evidence. 4 , 11 , 14 , 32 As is typical for surgical management of orthopedic conditions, it is hard to reduce the risk of bias for surgical interventions. A narrative review is discussed regarding the most current and relevant literature on AED.…”
Section: Resultsmentioning
confidence: 99%
“…After a simple elbow dislocation, a protective brace is often used to lock the elbow at 90° of flexion for the first 1-3 weeks to limit extension and to avoid varus stress on the lateral collateral ligament (8). However, early mobilization after simple elbow dislocation resulted in an expedited return of ROM, function and return to work (25). Importantly, in either scenario, the severity of the damaged structures, motivation of the patient, and pain play a major role in the strategy a clinician chooses.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review of the literature confirmed early return of range of motion and function, as well as quicker return to work, in patients with early mobilization after dislocation 3 . Animal studies have added to the evidence for this approach to simple elbow dislocation.…”
Section: Commentarymentioning
confidence: 91%